2018
DOI: 10.1136/bmjopen-2017-019650
|View full text |Cite
|
Sign up to set email alerts
|

Femoral Nerve Block Intervention in Neck of Femur Fracture (FINOF): a randomised controlled trial

Abstract: ObjectiveFractured neck of femur is a severely painful condition with significant mortality and morbidity. We investigated whether early and continuous use of femoral nerve block can improve pain on movement and mobility after surgery in older participants with fragility neck of femur fracture.DesignProspective single-centre, randomised controlled pragmatic trial.SettingSecondary care, acute National Health Service Trust, UK.ParticipantsParticipants admitted with a history and examination suggesting fractured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 29 publications
1
40
0
Order By: Relevance
“…The fractures of the proximal femur, including the fracture of the neck of femur, intertrochanteric, and subtrochanteric fractures, are a common orthopedic emergency, especially in the geriatric population [1]. These fractures are extremely painful and associated with significant morbidity and mortality [2,3]. Regional anesthesia is preferred during surgery in these patients.…”
Section: Introductionmentioning
confidence: 99%
“…The fractures of the proximal femur, including the fracture of the neck of femur, intertrochanteric, and subtrochanteric fractures, are a common orthopedic emergency, especially in the geriatric population [1]. These fractures are extremely painful and associated with significant morbidity and mortality [2,3]. Regional anesthesia is preferred during surgery in these patients.…”
Section: Introductionmentioning
confidence: 99%
“…Full text screening was performed in 118 of these studies and after this procedure 15 studies were found to fulfil the inclusion criteria [ 15 29 ]. However, three trials were subsequently excluded; one trial was only published as a detailed abstract and the author did not respond to our inquiry of supplementary data [ 24 ]; one study had to be excluded due to the participants in the intervention group not being randomised directly to US-PNBs [ 25 ] and one trial [ 26 ] permitted a single shot US-guided femoral nerve block as rescue treatment in the standard care (control). Most common reasons for exclusion at full text screening were no US-guidance, not RCT or wrong comparator.…”
Section: Resultsmentioning
confidence: 99%
“…In total, twenty-five studies met the inclusion criteria[12, 14, 16, 20, 23, 27, 28, 33, 34, 38, 47, 51, 59, 60, 62, 65, 57, 66, 74, 77, 80, 82, 83, 85, 86]. Included studies date from 2007 to 2019.…”
Section: Resultsmentioning
confidence: 99%